Persepsi Pemustaka terhadap Sikap Pustakawan Layanan Sirkulasi di Perpustakaan Kota Yogyakarta - Asnawi Asnawi (Jurnal Adabiya, 2018)
Public library of Yogyakarta is a public space open for people and become a place for Yogyakarta’s people to read, discuss and study. Library service must be organized maximumly to meet people’s satisfaction. The ability to produce a good service is a main requirement of librarian especially for circulation service staff. Circulation service is a main core of the library. This research is aimed to know the perception of user on li- brarian’s attitude in circulation service. This research used the quantitative descriptive method. The result of research in circulation service in city library using skill based is good enough. This can be seen from the respon of librarian in giving good informations, the service is also meet the expectation of the users, librarian’s atti- tude is showing care, kind and fun. But the respon on book demand and positive inputs from users still need to be improved